2004
DOI: 10.1242/jcs.01379
|View full text |Cite
|
Sign up to set email alerts
|

New sorting nexin (SNX27) and NHERF specifically interact with the 5-HT4(a) receptor splice variant: roles in receptor targeting

Abstract: ). Most of them are scaffolding proteins that contain several structural interaction domains such as Src homology 2 (SH2) or 3 (SH3) domains, post-synapticdensity-95/disc-large/zonula-occludens-1 (PDZ) domains and Drosophila enabled and vasodilator-stimulated phosphoprotein homologous (EVH) domains. These proteins participate in the building of large submembrane protein signaling networks. We have recently isolated a complex of at least 15 proteins interacting with the C-terminal tail of the 5-HT2C receptor, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
140
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(153 citation statements)
references
References 40 publications
11
140
0
1
Order By: Relevance
“…Indeed, a 15-min stimulation of the receptor was sufficient to induce receptor trafficking to a perinuclear compartment, where the receptor bound by arrestin was retained for Ͼ6 h. This behavior clearly classifies the 5-HT 4 Rs into class B GPCRs (33). We have recently reported that 5-HT 4 Rs are associated with a series of GPCR-interacting proteins, including SNX-27 (sorting nexin-27) and the Na ϩ /H ϩ exchanger regulatory factor (61). Although the role of GPCR-interacting proteins in 5-HT 4 R endocytosis and recycling remains to be analyzed, they have been shown to be clearly implicated in other GPCR systems (62,63).…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, a 15-min stimulation of the receptor was sufficient to induce receptor trafficking to a perinuclear compartment, where the receptor bound by arrestin was retained for Ͼ6 h. This behavior clearly classifies the 5-HT 4 Rs into class B GPCRs (33). We have recently reported that 5-HT 4 Rs are associated with a series of GPCR-interacting proteins, including SNX-27 (sorting nexin-27) and the Na ϩ /H ϩ exchanger regulatory factor (61). Although the role of GPCR-interacting proteins in 5-HT 4 R endocytosis and recycling remains to be analyzed, they have been shown to be clearly implicated in other GPCR systems (62,63).…”
Section: Discussionmentioning
confidence: 91%
“…The low BRET signal observed with the h5-HT 4(g) R-RLuc construct suggests that the C-terminus of this splice variant may influence the spatial organization of the Rluc and therefore the intensity of the energy transfer between the donor and the acceptor. It is interesting to note that the mouse 5-HT 4(e) R splice variant specifically binds with its C-terminus to several PDZ-domain containing proteins [25]. Since the h5-HT 4(g) R is very similar to the mouse 5-HT 4(e) R and also contains a canonical recognition motif for PDZ domains at their extreme C-termini [25], it is therefore likely that the presence of these PDZdomain containing proteins in the h5-HT 4(g) R modifies the relative distance and orientation of Rluc and YFP within dimers in such a way that no significant energy transfer is detectable.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that the mouse 5-HT 4(e) R splice variant specifically binds with its C-terminus to several PDZ-domain containing proteins [25]. Since the h5-HT 4(g) R is very similar to the mouse 5-HT 4(e) R and also contains a canonical recognition motif for PDZ domains at their extreme C-termini [25], it is therefore likely that the presence of these PDZdomain containing proteins in the h5-HT 4(g) R modifies the relative distance and orientation of Rluc and YFP within dimers in such a way that no significant energy transfer is detectable. Results obtained in membranes prepared from these cells support this interpretation since specific BRET signals have been observed in these preparations most likely due to the lost of the PDZ domain containing proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 cargo proteins including a number of GPCRs such as the β2-adrenoceptor, 5HT 2 receptor and parathyroid hormone receptor (78)(79)(80). Detailed proteomic analysis conducted in mammalian cell lines has revealed that a loss of SNX27 expression results in the downregulation of multiple membrane proteins (81).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%